jurnal akuntansi dan bisnis PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL, DAN KOMISARIS INDEPENDEN TERHADAP KINERJA KEUANGAN PERUSAHAAN - VIVIAN DEWI SETYANINGSIH YULIATIN (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
This study aims to examine the effect of firm size, managerial ownership, and independentcommissioners on the company's financial performance. This study uses a population of allmanufacturing companies listed on the Indonesia Stock Exchange. The number ofmanufacturing companies sampled using the purposive sampling method was obtained as many as 40companies with a research period of 4 years. The analysis technique used is multiple linearregression analysis. The results of hypothesis testing indicate that firm size, managerial ownership,and independent commissioners have a significant positive effect on the company's financialperformance.